Enfermedades del cultivo de haba (Vicia faba L), en la parroquia El Ángel, cantón Espejo, Carchi. - Yandún Godoy, Estalin Mauricio (2023)
The broad bean is a typical crop from the highlands of Ecuador, which belongs to the legume family, its consumption is very popular throughout the country, both in green pods and dry grains. The purpose of this research work was to determine the diseases that affect the broad bean crop, in the El Ángel parish, Espejo canton, Carchi. In order to carry out adequate and timely control, which reduces the rate of damage to the crop, improving production results and profitability for the producer. The diseases that cause damage to the broad bean crop and are the biggest problem for producers in the area are: Chocolate spot (Botrytis fabae), Ascochyta spot, root rot and Rust (Uromyces fabae). The chocolate spot is considered the most important disease in broad bean cultivation, it presents circular or oval chocolate-brown spots on the upper side and underside of the leaves, it can also occur on the stems, flowers and fruits, when environmental conditions are favourable. Most of the producers sow the machetona criolla variety, using chemical products to control diseases and, in addition, the producers in the study area have not received training on the correct use of fungicides